Particleboard from agricultural biomass and recycled wood waste: a review - Lee, Seng Hua; Lum, Wei Chen; Boon, Jia Geng; Kristak, Lubos; Antov, Petar; Pędzik, Marta; Rogoziński, Tomasz; Taghiyari, Hamid R.; Lubis, Muhammad Adly Rahandi; Fatriasari, Widya; Yadav, Sumit Manohar; Chotikhun, Aujchariya; et al. (Elsevier BV, 2022)
The use of alternative raw materials such as agricultural biomass and recycled wood waste and by-products in particleboard production is a viable approach to respond to the increased global demand for wood-based materials, and it is a key circular economy principle as well. Wood chips are the second most costly element after resin in particleboard production, where both elements accounting for more than 50% of the overall production cost. Therefore, a significant cost reduction could be achieved by replacing wood chips with lignocellulosic agricultural wastes. Agricultural biomass exists in abundant post-harvest and post-production processes and can be served as an ideal alternative for particleboard manufacturing. This study aimed to review and evaluate the current state-of-the-art particleboard production using a wide variety of environmentally-friendly agricultural biomass, recycled wood waste, and by-products. In this review, the agricultural biomass used for particleboard production was classified into seven different groups based on the part of the plant which they are extracted from, i.e. straw, stalk, bagasse, seed/fruit, leaf, grass, and palms. Particleboards' properties of these raw materials were also compared in terms of their mechanical parameters. The last part of this review concluded the challenges and future potential of using agricultural biomass and recycled wood waste.